Parenting Ekonomi: Edukasi Finansial Bagi Anak Usia Dini - Erika Astriani Aprilia; Dea Annisa; Nurbaeti Nurbaeti (Universitas Pamulang, 2021)
Parents are the first source who must introduce children to how to manage finances well. The importance of financial literacy education in children, how to instill effective financial literacy values in children, and the role of families and schools to instill financial literacy educational values in children need to be narrated back to the community. This community service is carried out to recitation mothers in the West Pamulang area, totaling approximately 40 people with the implementation method in the form of counseling or lectures, and discussions. The results of PKM activities obtained data that most of the participants had not provided financial education for their children. After participating in this activity, participants have learned the tips and efforts in educating the values of financial literacy to their children from an early age.